çŽ°ä»£æ±‰è¯ä¸Žå°å°¼è¯äººç§°ä»£è¯å¯¹æ¯”ç ”ç©¶ - Asmuliyati Nahnu (Universitas Negeri Makassar, 2023)
æ‘˜è¦Â æœ¬æ–‡ç ”ç©¶çš„å¯¹è±¡æ˜¯çŽ°æ±‰å°å°¼è¯çš„äººç§°ä»£è¯çš„ä¸‰ç±»ï¼ŒåŒ…æ‹¬ç¬¬ä¸€äººç§°ä»£è¯ã€ç¬¬äºŒäººç§°ä»£è¯å’Œç¬¬ä¸‰äººç§°ä»£è¯ã€‚æœ¬æ–‡å¯¹çŽ°æ±‰å°å°¼è¯äººç§°ä»£è¯çš„ç ”ç©¶æ–¹æ³•è¿ç”¨è¯è¨€å¯¹æ¯”åˆ†æžç†è®ºã€è¯ä¹‰å’Œè¯ç”¨åˆ†æžç†è®ºæ¥è¿›è¡Œåˆ†æžã€‚æœ¬æ–‡å¯¹æ¯”ç ”ç©¶çš„ç»“æžœæŒ‡å‡ºä¸ä»…ä»Žè¯è¯æ–¹é¢ä¹Ÿä»Žä½¿ç”¨åŠŸèƒ½æ–¹é¢çŽ°ä»£æ±‰è¯å’Œå°å°¼è¯äººç§°ä»£è¯éƒ½æœ‰å¼‚åŒç‚¹ã€‚çŽ°æ±‰å°å°¼è¯äººç§°ä»£è¯çš„ç›¸åŒç‚¹ï¼šæœ‰æŽ’é™¤å¼å’ŒåŒ…æ‹¬å¼ï¼Œæœ‰äººç§°ä»£è¯å•å¤æ•°è½¬æ¢å½¢å¼ï¼Œæ²¡æœ‰ç”·å¥³æ€§åˆ«çš„åŒºåˆ«ï¼Œæœ‰æ•¬ç§°å¼ã€‚è€ŒçŽ°æ±‰å°å°¼è¯äººç§°ä»£è¯çš„ä¸åŒç‚¹ï¼šå¤æ•°å½¢å¼ï¼Œæ„Ÿæƒ…è‰²å½©ï¼Œè¯æ³•ä¸ŠåŠŸèƒ½ï¼Œå®šè¯è¯åºã€‚Â å…³é”®è¯: çŽ°ä»£æ±‰è¯ã€å°å°¼è¯ã€äººç§°ä»£è¯ã€å¯¹æ¯”åˆ†æž.Â ABSTRACTÂ The object of this paper is the three types of personal pronouns in modern Chinese Indonesian, including first-person pronouns, second-person pronouns and third-person pronouns. This paper analyzes the research methods of personal pronouns in Chinese and Indonesian by using the theory of linguistic contrastive analysis, semantic and pragmatic analysis. The results of the comparative study in this paper point out that there are similarities and differences between modern Chinese and Indonesian personal pronouns not only in terms of words but also in terms of usage functions. The similarities between Chinese and Indonesian personal pronouns: there are exclusionary and inclusive forms, personal pronouns can be converted into plural and singular, there is no distinction between male and female, and there are respectful forms. However, the differences between personal pronouns in Chinese and Indonesian languages are: plural form, emotional color, grammatical function, attributive word order.Â Key words: modern Chinese, Indonesian language, Personal pronouns, Contrastive analysis